Sensitivity of peripheral blood lymphocytes to adrenaline and acetylcholine in patients with primary and recurrent posterior uveitis (Ukrainian Journal of Ophthalmology, 2025)
Background: Posterior uveitis is a polyetiologic group of diseases with polymorphic clinical manifestations and a prolonged, chronic and recurrent course. In addition, it is commonly bilateral and often causes complications, loss of working capacity and early visual disability in young adults. It is an important task of current clinical ophthalmology to find biomarkers indicating the severity of inflammation and the likelihood of developing a recurrence of the initial process.Purpose: To determine the sensitivity of peripheral blood lymphocytes to adrenaline and acetylcholine in patients with primary and recurrent uveitis at different phases of the disease.Material and Methods: One hundred patients with idiopathic posterior uveitis were examined at different phases of the disease. The control group was composed of 16 healthy individuals of a similar age. The specific sensitivity of lymphocytes to neuromediators, adrenaline and acetylcholine (expression of T cell adrenergic and acetylcholine receptors) was assessed using our complex methodology (in conjunction with a parallel sampling method) for assessing the individual’s sensitivity to medicaments (biological regulators) which has been developed at Immunology laboratory, Filatov Institute of Eye Disease and Tissue Therapy. The method involves obtaining lymphocytes from an individual, culturing lymphocytes with examined drugs immunohistochemically, and use of a peroxidase anti-peroxidase method with monoclonal T-cell antibodies.Results: Absolute and relative adrenoreceptor and acetylcholine receptor expression levels in patients with posterior uveitis were 1.8-2.0 times and 1.6-2.4 times, respectively, higher in patients with posterior uveitis compared to controls. Absolute adrenoreceptor and acetylcholine receptor expression values were 12.6% and 31.7%, respectively, higher in the recurrent process during active inflammation compared to the period of remission. However, in patients with posterior uveitis, adrenoreceptor and acetylcholine receptor expression values in the period of remission were still higher than normal values. The odds of an increased relative adrenoreceptor expression and the odds of an increased relative acetylcholine receptor expression on peripheral blood lymphocytes were 67.5-fold higher and 23.6-fold higher, respectively, among patients with posterior uveitis compared to controls. The correlation of adrenoreceptor expression and acetylcholine receptor expression with absolute counts of T cells and T helpers was stronger than the correlation with B cells, which reflects to a larger extent the association with the cellular immunity and to a lesser extent the association with the humoral immunity. There was a moderate correlation of adrenoreceptor expression and acetylcholine receptor expression with cell subsets of markers of early lymphocyte activation CD5, autoimmune aggression CD25, intercellular adhesion CD54 and apoptosis CD95 (Fas/APO-1).Conclusion: The adrenoreceptor expression and acetylcholine receptor expression on peripheral blood lymphocytes may be used as a non-specific biomarker of an activated inflammatory process in posterior uveitis.
Keywords: posterior uveitis; adrenaline; acetylcholine; lymphocyte activation biomarkers